Growing up in Australia: The longitudinal study of Australian children: The first decade of life - Edwards, Ben (My University, 2012)
This article provides an overview of the Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC) study design and the first five waves of data collection for the study. It illustrates how LSAC data have been used in a wide range of research.
Family Matters
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology